(untitled) (London Journal of Engineering Research, 2024)
The curing of urea-formaldehyde resin in the presence of urea used to reduce the formaldehyde content in particleboards was researched. Free urea was added into the adhesive with different amounts of latent curing agent (1 and 3% ammonium sulfate based on dry resin); a urea which is part of the modifiers-curing agents (products of the interaction of citric acid, urea and ammonia) was also studied separately. Based on the results of differential scanning calorimetry, solid-state NMR 13C of the cured resin and tests of model particleboards, it was suggested that the effect of urea is significantly influenced by the pH value of the adhesive before and during curing. At a relatively high pH value (3.50-3.70 after curing at ammonium sulfate content of 1%), urea acts as a classical scavenger, that is, it chemically interacts with formaldehyde to form harmless products. At a reduced pH value (3.00-3.10 after curing at ammonium sulfate content of 3%), urea reacts with resin components (methylolureas and UF oligomers mainly) that is, it participates in the curing of the adhesive. Tests of model samples of particleboards have shown that the mechanism of including urea into the structures of the curing resin is less effective for reducing toxicity than its action as a classical scavenger; at the same time, the formaldehyde content in particleboards with 3% ammonium sulfate and urea is lower in absolute values due to the useful effect of the curing agent. Modifiers-curing agents provide a low pH value of the binder before curing (3.72-4.51 with a content of modifiers-curing agents of 5%), urea in their composition is also involved in curing (according to solid-state NMR data).